Shifting Aesthetics: Why "Appropriateness" is the New Goal of Artistic Research in Design - Winta Adhitia Guspara (IJCAS (International Journal of Creative and Arts Studies), 2025)
This article is another facet of my thesis, a reflection on the process I've been through. I aim to bring the concept of "appropriateness" to life more fully in the realm of artistic research, which inherently encompasses not only functional aspects but also aesthetic, ethical, and moral considerations. Through this more profound understanding of appropriateness, the debate about what is "useful" and what is "good" shifts to a more fundamental and principled question: what is "true and meaningful." I address this understanding through the lens of design and ergonomics, which makes the body the determining subject, rather than the object to be measured. The argument I develop is a rethinking of the interaction between the body and the tool/product, beyond mere mechanics, to embody the body as a medium for generating design knowledge. This knowledge is divided into two categories: tacit knowledge and embodied knowledge, which will be integral to the development of user experiences.The investigation in my thesis involved participants with spinal cord injuries resulting from work accidents, traffic accidents, and disaster survivors, who ultimately suffered paraplegia. The approach used was ethnography, specifically participant observation and ethnographic interviews, combined with the principles of somaesthetic design. During the investigation and design of mobility aids, shifts in sensation were identified as a form of user experience that occurs when the device/product is modified. The process of individuals with paraplegia fighting for the fundamental right to mobility involves social, ethical, functional, and aesthetic considerations. Based on my reflection on this research experience, I have developed a hypothesis about how to design user experiences through the principles of somatic work, which shape bodily experiences and are translated into design. The situation is more encouraging from my reflection on conducting research with those who have paraplegia, in that I learned how not to become a parasitic researcher. Pergeseran Estetika: Mengapa “Kesesuaian” Merupakan Tujuan Baru Penelitian Artistik dalam Desain AbstrakArtikel ini merupakan aspek lain dari tesis saya, sebuah refleksi atas proses yang telah saya lalui. Saya bertujuan untuk menghidupkan konsep "kesesuaian" secara lebih utuh dalam ranah penelitian artistik, yang secara inheren mencakup tidak hanya aspek fungsional tetapi juga pertimbangan estetika, etika, dan moral. Melalui pemahaman yang lebih mendalam tentang kesesuaian ini, perdebatan tentang apa yang "berguna" dan apa yang "baik" bergeser ke pertanyaan yang lebih fundamental dan berprinsip: apa yang "benar dan bermakna". Saya membahas pemahaman ini melalui lensa desain dan ergonomi, yang menjadikan tubuh sebagai subjek penentu, alih-alih objek yang diukur. Argumen yang saya kembangkan adalah pemikiran ulang tentang interaksi antara tubuh dan alat/produk, melampaui sekadar mekanika, untuk mewujudkan tubuh sebagai media untuk menghasilkan pengetahuan desain. Pengetahuan ini dibagi menjadi dua kategori: pengetahuan tersirat dan pengetahuan yang diwujudkan, yang akan menjadi bagian integral dalam pengembangan pengalaman pengguna.Investigasi dalam tesis saya melibatkan partisipan dengan cedera tulang belakang akibat kecelakaan kerja, kecelakaan lalu lintas, dan penyintas bencana, yang akhirnya menderita paraplegia. Pendekatan yang digunakan adalah etnografi, khususnya observasi partisipan dan wawancara etnografi, yang dipadukan dengan prinsip-prinsip desain somaestetik. Selama investigasi dan perancangan alat bantu mobilitas, pergeseran sensasi diidentifikasi sebagai bentuk pengalaman pengguna yang terjadi ketika perangkat/produk dimodifikasi. Proses individu dengan paraplegia memperjuangkan hak fundamental untuk mobilitas melibatkan pertimbangan sosial, etika, fungsional, dan estetika. Berdasarkan refleksi saya terhadap pengalaman penelitian ini, saya telah mengembangkan hipotesis tentang bagaimana merancang pengalaman pengguna melalui prinsip-prinsip kerja somatik, yang membentuk pengalaman tubuh dan diterjemahkan ke dalam desain. Situasi ini lebih menggembirakan dari refleksi saya dalam melakukan penelitian dengan mereka yang memiliki paraplegia, karena saya belajar bagaimana untuk tidak menjadi peneliti parasit.